Maize (Zea mays) barrier as a cultural method for management of thrips in Onion (Alliuln cepa) - SRINTVAS, P S; ELAWANDE, K (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during rabi 200 1-2004 using maize (Zea maize L.) plants as barrier for blocking migrating adult thrips in onion (Allium cepa L.) at Rajgurunagar, Maharashtra. Live barrier crops used surrounding onion are 2 rows of maize, an outer row of maize + an inner row of wheat and 2 rows of wheat. Onion crop with nlaize and maize+wheat as barriers found very effective in blocking adult thrips and recorded 77.67 and 75.34 % blockage respectively. Barrier crop of wheat could block only 45.52 percent ofadult thrips. At 100 cnl height blocking by maize barrier is higher than in maize + wheat barrier. Lowest number of thrips was recorded in maize barrier (9.8/plant) followed by maize + wheat barrier (10.9/ plant) compared to onion without barrier that recorded 32.4 thrips/plant. Maize barrier around 250 1112 of onion crop did not cause shading effect and yielded higher than plots with no barrier. Insecticide application can be minimized considerably using barrier crop in onion for thrips management.